Pengaruh Profitabilitas, Leverage dan Struktur Modal terhadap Financial Distress Perusahaan Sektor Consumer Non-Cyclical yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Dhea Puspitasari; Dani Sopian (Universitas Nusantara PGRI Kediri, 2025)
This study aims to examine the effect of profitability, leverage, and capital structure on financial distress in non-cyclicals consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Profitability is measured by return on assets (ROA), leverage is measured by the debt to asset ratio (DAR), and capital structure is measured by the debt to equity ratio (DER), while financial distress is assessed using the Springate Score. This research employs a quantitative method. The sample was selected using purposive sampling, resulting in 63 companies as the observation sample. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The R Square value obtained is 0.631, indicating that 63.1% of the variation in financial distress can be explained by profitability, leverage, and capital structure, while the remaining 36.9% is explained by other factors outside the model.The results show that profitability has a significant positive effect on financial distress, whereas leverage and capital structure have a significant negative effect on financial distress.